Medievalism in A Song of Ice and Fire and Game of Thrones - Carroll, Shiloh, 1980- (Medievalism, 2018)
Game of Thrones is famously inspired by the Middle Ages - but how authentic is the world it presents? This volume offers different angles to the question.